Criminal Sanctions On Illegal Logging Crime In State Court Of Semarang - Muslich Ashari; Amin Purnawan; Achmad Sulchan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The formulation of the problem discussed in this study were (1). How settings Criminal Law on Illegal logging?, (2). How Judges consideration in decisions on Illegal logging in State Court of Semarang?. (3). Are the constraints faced by the judge in deciding the case of Illegal logging?.This research used socio-juridical legal research, research data was taken by interview with the respondent judges handling crime of Illegal logging State Court of Semarang. This research use Qualitative analysis techniques.Conclusion of this study is illegal logging is a special crime and therefore their specific legislation governing of illegal logging, in Act No. 18 of 2013 on Combating And Preventing The Destruction Of Forests set of sanctions for Illegal logging in the form of punishment imprisonment for the perpetrators in the form of a sentence of imprisonment and fines, consideration of Judges in deciding the case of Illegal logging legally is appropriate that the elements are there that the perpetrator does not have a valid license from the clerk to do cutting trees in the forest area of Silayur, Judge obstacle in deciding the case of Illegal logging in the form of difficulties in distinguishing between illegal logging carried out by individuals and corporations, lack of special education for judges to handle crime of Illegal LoggingKeywords: Criminal Sanctions; Penalty; Illegal Logging.